2009
DOI: 10.1002/art.24267
|View full text |Cite
|
Sign up to set email alerts
|

Survival in pulmonary hypertension associated with the scleroderma spectrum of diseases: Impact of interstitial lung disease

Abstract: Objective. Pulmonary hypertension (PH) is an important cause of mortality in systemic sclerosis (SSc), where it can be isolated (pulmonary arterial hypertension [PAH]) or associated with interstitial lung disease (ILD). This study was undertaken to characterize determinants of survival among SSc patients with either type of PH who received PAH-specific therapy.Methods. Consecutive SSc patients with PAH or ILD-associated PH confirmed by right heart catheterization were included in the study. Kaplan-Meier and Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
174
2
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 229 publications
(198 citation statements)
references
References 80 publications
14
174
2
3
Order By: Relevance
“…However, available data suggest that patients with pulmonary hypertension associated with ILD have a 5-fold increased risk of death compared with patients with PAH in spite of the use of endothelin receptor antagonists (30).…”
Section: Discussionmentioning
confidence: 99%
“…However, available data suggest that patients with pulmonary hypertension associated with ILD have a 5-fold increased risk of death compared with patients with PAH in spite of the use of endothelin receptor antagonists (30).…”
Section: Discussionmentioning
confidence: 99%
“…Patients in whom PAH therapy had been initiated prior to diagnostic RHC and patients who were referred after starting PAH therapy were excluded. Some of the patients from the Johns Hopkins site have been described in a previous report (6).…”
Section: Methodsmentioning
confidence: 99%
“…Several recent clinical reports have highlighted the prognostic impact of pulmonary hypertension (PH) combined with ILD (5-7). While SSc patients with ILD alone have a median survival of 5-8 years (8), survival is significantly shortened with the development of PH (PH-ILD), as we and other investigators have recently suggested (6,9). In multivariate analyses, PH-ILD in SSc patients was associated with a 5-fold increased risk of death as compared to SSc-related PAH (6).…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Isolated survival of SSc patients with PAH while receiving pulmonary vasodilator therapy was recently reported to be 78% (1-year rate), 68% (2-year rate), and 47% (3-year rate) (7,19,20). Importantly, Tolle and coworkers have suggested that exercise-induced pulmonary hypertension (PH) may represent an intermediate phenotype "between" normal and resting PH (21).…”
Section: Methodsmentioning
confidence: 99%